2021
DOI: 10.1007/s44197-021-00020-6
|View full text |Cite
|
Sign up to set email alerts
|

Senile Cataract in Patients with Diabetes with and Without Diabetic Retinopathy: A Community-Based Comparative Study

Abstract: Aim We compare the incidence rates of cataract in persons with diabetes with and without diabetic retinopathy in Saudi Arabia, for the first time. In addition, we explored the role of new factor, diabetes age of onset and several other known factors. Methods In a community-based cross-sectional study, 334 persons with diabetes type 2 were randomly selected from a diabetic register. Detailed history and comprehensive ophthalmic examination was done at an ey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
2
3
0
1
Order By: Relevance
“…Olafsdottir et al showed that the prevalences of significant cortical, posterior subcapsular, and nuclear cataracts were 65.5%, 42.5%, and 48.0%, respectively, in the type 2 diabetes population [ 5 ]. These results are consistent with most of the previous studies [ 6 , 7 , 8 , 9 , 10 ]. Two studies reported contrasting findings, that is, NS was identified as the predominant subtype [ 3 , 11 ].…”
Section: Introductionsupporting
confidence: 94%
“…Olafsdottir et al showed that the prevalences of significant cortical, posterior subcapsular, and nuclear cataracts were 65.5%, 42.5%, and 48.0%, respectively, in the type 2 diabetes population [ 5 ]. These results are consistent with most of the previous studies [ 6 , 7 , 8 , 9 , 10 ]. Two studies reported contrasting findings, that is, NS was identified as the predominant subtype [ 3 , 11 ].…”
Section: Introductionsupporting
confidence: 94%
“…Consistently, a community-based cross-sectional study done in Saudi Arabia showed that among 668 eyes from 334 patients with T2DM, 237 eyes (35.5%) had cataract (28). Similar to the findings of Becker et al, diabetic patients with cataract were associated with a longer duration of diabetes.…”
Section: Epidemiology Of Diabetic Macular Edemasupporting
confidence: 76%
“…Other studies by Alabdul Wahhab KM et al and Wen L et al reported cataract prevalence rates of 35.5% and 36.4%, respectively, which are lower than the findings of this study. 4,5 The higher prevalence of cataract in this population highlights the need for specific awareness programs and interventions to reduce their occurrence. Although diabetes may not be the direct cause of cataract, it is known to be a contributing factor.…”
Section: Discussionmentioning
confidence: 99%